Damage Detection in CFRP Plates Using Spectral Entropy. (20th May 2014) - Castro, E.; Moreno-García, P.; Gallego, A.
Abstract : Damage detection techniques using vibrations are based on measuring the changes in the vibration parameters of a structure. This paper studies the viability of the spectral entropy as a new damage detection parameter to detect the presence of damage in a composite fiber reinforced polymers (CFRP) plate. To carry out this study, the vibrations in a CFRP plate with and without damage were measured and the correlation between damage and spectral entropy has been researched.